Analysis Of Public Services In Villages Mekarmulya Panyileukan District Bandung - Datu, Fefrina Tangke; Fatihah, Dian Candra (Transforma Jurnal Manajemen, 2025)
The title of this "research is Analysis of Public Services in Mekarmulya Village, Panyileukan District, Bandung City. This article aims to analyze public services in Mekarmulya Village. The quality of public services is the level of public satisfaction with services provided by the government or public institutions.This study employed a qualitative method to analyze public services in Mekarmulya Village, Panyileukan District. Data collection techniques included in-depth interviews and observations. The analysis concluded that efforts to improve the quality of public services in Mekarmulya Village are needed to meet community needs and increase public trust.The obstacle I encountered was the lack of queue numbers, which left people dissatisfied and forced to wait long hours due to a lack of clear information. My suggestion was to create a simple, manual queue number system and optimize the use of existing resources to improve service efficiency